The Effect of Service Quality and Promotion on Customer Satisfaction at Hotel Ibis Padang - Rafika Elena; Azmen Kahar; Dewi Anggraini (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Customer satisfaction is a strategic concern for Hotel Ibis Padang, a three-star property affiliated with the Accor network, where occupancy figures between July and December 2025 fluctuated month to month while guest reviews repeatedly flagged issues such as inconsistent staff conduct, delayed room preparation, and poorly maintained in-room facilities. Motivated by these field indications, this study investigates whether service quality and promotion influence customer satisfaction, both individually and jointly. An associative-causal quantitative design was applied through a survey instrument distributed to 100 respondents, selected via purposive sampling with the sample size determined using the Slovin formula, targeting guests who had stayed at the hotel at least once. Responses were gathered using a five-point Likert-scale questionnaire and processed in SPSS version 26.00 through multiple linear regression. Findings reveal that service quality exerts a positive and statistically significant influence on customer satisfaction, as does promotion, and their combined effect likewise proves significant, accounting for 96.5 percent of the variance observed in satisfaction levels. Between the two predictors, service quality emerges as the stronger determinant. Based on these results, hotel management is encouraged to sustain ongoing service quality improvements and to diversify its promotional efforts as complementary strategies for maintaining guest satisfaction.